Evaluation of prognostic predictors of mangled extremity severity scoring system on the outcome of traumatic extremities injuries at emergency department in Suez Canal University Hospitals - Essa, Ahmed A.; El-Shaboury, Islam M.; El-Beltagy, Yasmin E. (International Surgery Journal, 2016)
Background:Severe traumatic lower limbs injuries have been associated with high incidence of multiple systems involved (integument, nerve, bone, and vascular structures). That’s make difficulty and stress on surgeon’s decision making either to amputate or preserve the injured limbs. The Mangled Extremity Severity Score (MESS) was developed in Seattle (Johansen et al), based on both retrospective and prospective analysis of admission data of patients with severe limb injuries. The objective of this study was to evaluation of the prognostic predicting factors of outcome of traumatic extremities patients using Mangled Severity Scoring System at Emergency Department in Suez Canal University Hospital in order to help surgeon to make decision either to preserve or to amputate. Methods: This is a descriptive study (cross sectional), conducted on 60 patients with severe extremities injuries that met the criteria of the Mangled Extremity Severity Scoring attending to the Emergency Department (ED) at Suez Canal University Hospital. Results:This study showed that 83.33% of the patients had associated fractures, 8.33% of them had pneumothorax, 5% of them had abdominal collection and 3.33% of them had brain injuries. This study showed that 75% of the studied patients had MESS less than 7 while 25% of them had MESS > or = 7. The Mangled scoring system was a good predictor of amputation among the studied patients with sensitivity of 71.4%, specificity of 100% and 90% accuracy. Conclusions:Most of the patients had Mangled Extremity Severity Score less than 7. The MESS showed statistically significant difference between the amputated and the not amputated patients with 90% accuracy in prediction of amputation.